Preparation of different heteroatom doped graphene oxide based electrodes by electrochemical method and their supercapacitor applications - Arvas, Melih Besir; Gursu, Hurmus; Gencten, Metin; Sahin, Yucel (ELSEVIER, 2021)
In this study, one-step preparation method of different heteroatom (-S, -N, -Cl) doped graphene oxide electrodes were achieved as electrode materials for the purpose of high-capacity supercapacitors. Microscopic, spectroscopic, and electrochemical methods were used to characterize the prepared electrodes. Formation of -ClO2, -ClO3, -SOx (x:2, 3) and -NO2 groups on the graphene oxide-based electrodes were determined by X-ray photoelectron spectroscopy analysis. Detail reaction mechanisms were suggested for the formation of these groups on the electrode surface for the first time in the literature. Different surface properties of graphene oxide structures in the electrodes were investigated by scanning electron microscopy and atomic force microscopy. Electrochemical behaviors of the prepared electrodes were characterized by cyclic voltammetry and electrochemical impedance spectroscopy. Sulphur, nitrogen, and chlorine doped graphene oxide electrodes were used as electrode materials for supercapacitor applications. Since different heteroatom doped graphene oxide-based electrodes showed different capacitive behavior. Areal capacitances of -S, -N and -Cl doped graphene oxide electrodes were determined as 206.4 mF.cm(-2), 533.2 mF.cm(-2) and 1098 mF.cm(-2), respectively with 10 mA. cm(-2).
Keywords: Supercapacitor; Graphene oxide-based supercapacitor; Heteroatom doped graphene oxide electrodes; Charge-discharge; Electrochemical supercapacitor; PENCIL GRAPHITE-ELECTRODES; ONE-STEP SYNTHESIS; FUNCTIONALIZED GRAPHENE; THERMAL-DECOMPOSITION; CARBON NANOTUBES; FACILE SYNTHESIS; AQUEOUS-SOLUTION; METHYLENE-BLUE; QUANTUM DOTS; URIC-ACID; Energy & Fuels